Analisis Perhitungan Tarif Perawatan Post Operasi Caesar Berdasarkan Metode Activity Based Costing pada Rumah Sakit Umum Anugrah Pangkajene Kabupaten Sidrap - Musdalifah Mulyadi; Hajrah Hamzah; Nurafni Oktaviyah (CV. ULIL ALBAB CORP, 2025)
This study analyzes the tariff applied by RSU Anugrah Pangkajene compared to the tariff calculated using activity-based costing (ABC) for post-cesarean wound care services. The approach used in this study is descriptive qualitative with the Activity-Based Costing (ABC) method to calculate the actual cost of the service. Data were collected through observation and interviews with medical records and hospital financial staff, as well as documentation related to the cost components of the service. The results of the study show that the tariff at RSU Anugrah for post-cesarean wound care is IDR 255,000, which is lower than the service tariff calculated using ABC, which results in an actual cost of IDR 689,150. However, the INA-CBG's tariff set by the Ministry of Health, amounting to IDR 202,600, is smaller compared to both tariffs. These findings highlight the need for the hospital to improve operational efficiency in activities with high costs and adjust service tariffs to better reflect the actual costs. This study provides a significant contribution by applying the ABC method, which can calculate tariffs more accurately and serve as a reference for decision-making on hospital service tariffs.